2021
DOI: 10.7181/acfs.2021.00031
|View full text |Cite
|
Sign up to set email alerts
|

Isolated temporalis muscle metastasis of renal cell carcinoma

Abstract: Isolated head and neck metastasis of renal cell carcinoma (RCC) is relatively rare and metastasis to the temple area is very rare. Here, we present the case of a 51-year-old man who was diagnosed with RCC 2 years earlier and had a contralateral metastatic temple area lesion. The patient who was diagnosed with renal cell cancer and underwent a nephrectomy 2 years ago was referred to the plastic surgery department for a temple mass on the contralateral side. In the operative field, the mass was located in the te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Nevertheless, the special location and surrounding structures of masseter muscles also determine special metastatic pathways. It is considered that, in addition to conventional arterial pathway and lymphatic pathway, vertebral venous plexus may be a special pathway of metastases at head and neck ( 15 ). Vertebral venous plexus connects with inferior vena cava and mesenteric vein.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the special location and surrounding structures of masseter muscles also determine special metastatic pathways. It is considered that, in addition to conventional arterial pathway and lymphatic pathway, vertebral venous plexus may be a special pathway of metastases at head and neck ( 15 ). Vertebral venous plexus connects with inferior vena cava and mesenteric vein.…”
Section: Discussionmentioning
confidence: 99%
“…However, some primary cancers also rarely exhibit spread to the scalp. Lee et al [ 9 ] reported a case of metastatic renal cell carcinoma in the head and neck area. To the best of our knowledge, only a few cases of cutaneous metastasis of gastric cancer in the head and neck area have been reported.…”
Section: Discussionmentioning
confidence: 99%